Hubungan Antara Motivasi Berprestasi Dengan Minat Membaca Buku Pada Siswa SMA Negeri 2 Klaten - Arendra, Suksmandi Surya (2016)
Interest of reading have an important role in language development and child intellectual which is can to think about expanding and also increasing knowledge for a good quality. This research head for find out: 1) Correllation between achieving motivation with student's interest of book reading 2) Student level of achieving 3) Student level of interested in reading 4) Effective contribution of achieving motivation and interested in book reading's student This research using randomly taken sample from member population with the random sampling method that as much as about 98 students. Research method with quantitative approaching with a measurement interested in book reading and achieving motivation scale. While data analysis using Product Moment by Pearson. Based on data analysis result, obtained rxy = 0,649 p = 0,000 ( p < 0,01 ), it mean hypotheses that acceptable filed or which is there is a very significant positive correlation between interested in book reading with achieving motivation. Level of achieving motivation included to high category with RE = 138,96 and RH = 117'5. And also interested in book reading level included to high category with RE = 92,25 and RH = 82'5. Effective achieving motivation donation toward interest of reading in the amount of 42,1% and 57,9, and the rest is influenced by another variable